2017
DOI: 10.1097/ijg.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy and Safety of the New Susanna Glaucoma Drainage Device in Refractory Glaucomas: Short-term Results

Abstract: Our initial findings suggest that the new SGDD is an effective alternative for managing neovascular and refractory glaucomas, with minor postoperative complications in the short-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…We found a success rate of 86.4% with at least 1 year of follow-up. Our results support the findings of a previous prospective study, 11 which reported a rate of success of 86% during a 6-month followup period.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found a success rate of 86.4% with at least 1 year of follow-up. Our results support the findings of a previous prospective study, 11 which reported a rate of success of 86% during a 6-month followup period.…”
Section: Discussionsupporting
confidence: 92%
“…The absence of early postoperative complications in our study could be partially because of the fact that all surgeries were done by one experienced surgeon in long-tube glaucoma implant surgery. In addition, one previous prospective study with multiple well-trained surgeons investigating the SGDD implant also found low rates of early complications (5.2%) 11…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations